2017
DOI: 10.1111/jfs.12342
|View full text |Cite
|
Sign up to set email alerts
|

The modeling of time to enterotoxin detection of Staphylococcus aureus in chicken meat

Abstract: This study was aimed to model the Time to Enterotoxin Detection (TED) in chicken meat as a function of temperature and salt concentration (NaCl) using a polynomial response surface model. The standard strain of Staphylococcus (ATCC 13565) as the producer of enterotoxin A producer was inoculated into 25 g of chicken meat sample. The samples were prepared according to proposed combinations of NaCl concentration, pH, and temperature with consider to the experimental design. At intervals of time, (1–24 hours), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
1
3
0
1
Order By: Relevance
“…In that study, temperature, pH value (5.9–6.2) and NaCl concentration (0.8–2.3%) were considered as experimental variables to establish the predictive model, the results of that study confirmed our previous assumption that the pH value and NaCl concentration had no significant effect on TTD. Accordance with our experimental design, temperatures and initial inoculating concentrations were chosen as the environmental variables, the result of correlation test showed that the temperature had a high negative correlation with TTD, which is consistent with the conclusions of Chaves et al ( 2017 ). The initial inoculating concentration also had negative correlation with TTD, but its correlation level was lower than that of temperature.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In that study, temperature, pH value (5.9–6.2) and NaCl concentration (0.8–2.3%) were considered as experimental variables to establish the predictive model, the results of that study confirmed our previous assumption that the pH value and NaCl concentration had no significant effect on TTD. Accordance with our experimental design, temperatures and initial inoculating concentrations were chosen as the environmental variables, the result of correlation test showed that the temperature had a high negative correlation with TTD, which is consistent with the conclusions of Chaves et al ( 2017 ). The initial inoculating concentration also had negative correlation with TTD, but its correlation level was lower than that of temperature.…”
Section: Discussionsupporting
confidence: 89%
“…Among the mathematical models used in predictive microbiology, linear polynomial regression is a useful method and has been widely used to predict the growth kinetics of bacteria (Zhao et al, 2002 ; Dong et al, 2007 ; Lee et al, 2015 ). The first use of polynomial regression to predict the enterotoxins was reported by Chaves et al ( 2017 ). In that study, temperature, pH value (5.9–6.2) and NaCl concentration (0.8–2.3%) were considered as experimental variables to establish the predictive model, the results of that study confirmed our previous assumption that the pH value and NaCl concentration had no significant effect on TTD.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of risk factors along the meat chain causing microbial contamination or growth [ 77 , 78 , 80 , 81 , 82 , 83 , 84 , 85 , 87 , 89 , 90 , 91 , 92 , 93 , 97 , 98 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ,…”
Section: Resultsmentioning
confidence: 99%
“…Одним із таких біологічних ризиків є ризик, пов'язаний із використання м'яса, отриманого від вимушено забитих тварин, яке може бути обсемінене небезпечними мікроорганізмами [1][2][3][4][5].…”
Section: вступunclassified